2009
DOI: 10.1002/ajpa.21188
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive ecology and the endometrium: Physiology, variation, and new directions

Abstract: Endometrial function is often overlooked in the study of fertility in reproductive ecology, but it is crucial to implantation and the support of a successful pregnancy. Human female reproductive physiology can handle substantial energy demands that include the production of fecund cycles, ovulation, fertilization, placentation, a 9-month gestation, and often several years of lactation. The particular morphology of the human endometrium as well as our relative copiousness of menstruation and large neonatal size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 184 publications
(269 reference statements)
0
40
0
Order By: Relevance
“…If women with higher ovarian hormone levels tend to have a more proliferative endometrial lining (98) and by extension, heavier, more regular menstrual bleeding, then their lower levels of PFOS and PFOSA may be attributable to greater clearance in menstrual blood (91, 99, 100). Indeed, in NHANES, levels of multiple PFASs were higher in post-menopausal women than premenopausal, and highest in women with hysterectomies (43, 101), suggesting that menstrual bleeding may be a major route of clearance of PFASs.…”
Section: Discussionmentioning
confidence: 99%
“…If women with higher ovarian hormone levels tend to have a more proliferative endometrial lining (98) and by extension, heavier, more regular menstrual bleeding, then their lower levels of PFOS and PFOSA may be attributable to greater clearance in menstrual blood (91, 99, 100). Indeed, in NHANES, levels of multiple PFASs were higher in post-menopausal women than premenopausal, and highest in women with hysterectomies (43, 101), suggesting that menstrual bleeding may be a major route of clearance of PFASs.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike most mammals, the uterine endometrium of human and some non-human primates undergoes cyclical monthly changes that result in the growth, angiogenesis and differentiation of the functional (proliferative) endometrium (Clancy 2009; Ramsey, et al 1976). Shifts in the synthesis and secretion of the ovarian steroids, estrogen and progesterone, during this menstrual cycle serve as the principal hormonal drivers for these changes.…”
Section: Uterusmentioning
confidence: 99%
“…With respect to foetal biology, placentation is more invasive (haemochorial) in simian primates (monkeys, apes, humans) than in rodents; that is, the feto-placental tissues are bathed directly in maternal blood without an intervening cellular barrier (Clancy 2009). It has been demonstrated that fatty acid (but not protein or carbohydrate) transfer from the mother to the foetus is greater in species with more invasive placentation (Elliot and Crespi 2008) and potentially, therefore, increases in glucocorticoid and other stress factor levels in the maternal circulation could also lead to more marked increases in these factors in the foetal circulation in species with more invasive placentation.…”
Section: Introductionmentioning
confidence: 99%